A Sigh of Mystery: Karl Barth's Theology of the Virgin Birth - Resch, Dustin (My University, 2010)
In this study, I examine Karl Barth's doctrine of the virgin birth of Christ in relation to his discussions in the Church Dogmatics of Christology, pneumatology and interpretation of Scripture. I argue that the virgin birth of Jesus Christ is understood by Barth as a fitting sign to expresses the form of the dialectic of God's "No" to sin and "Yes" to humanity in his free act of revelation and reconciliation. As such, the doctrine of the virgin birth functions for Barth as a paradigm through which to understand the fashion of God's work upon human beings and the suitable posture of a human being before God. I demonstrate this conviction by providing an overview of select interpreters of the doctrine of the virgin birth in the western Christian tradition in order to set Barth's contribution in its theological context. I then provide an exposition of the methodological and exegetical features of Barth's development of the doctrine of the virgin birth from his first professorship up to the introductory volume of the CD. Next, I examine how Barth's doctrine of the virgin birth fit with his broader Christology and pneumatology as represented in the CD. Finally, I provide an exposition of Barth's treatment of the figure of Mary as a capstone to the themes previously outlined. The thesis concludes with a series of probing questions about the implications of Barth's doctrine of the virgin birth for his broader theology.
title: A Sign of Mystery: Karl Barth's Theology of the Virgin Birth, author: Dustin Resch, location: Mills